β-lactam resistance in coagulase-negative Staphylococcus isolated from subclinical goat mastitis - Lucas, Amanda Pereira; Silva, Elizabete Cristina da; Farias, Andriele Renata Barbosa de; Albuquerque, Maria Priscilla Borges de; Lopes, Luciana Florêncio Vilaça; Barbosa, Severino Benone Paes; Batista, Ângela Maria Vieira; Mendonça, Marcelo; Pinheiro, Raymundo Rizaldo; Boechat, Jorge Ubirajara Dias; Silva, Elizabete Rodrigues da (Pesquisa Agropecuaria Brasileira, 2021)
The objective of this work was to evaluate resistance mechanisms to β-lactam antimicrobials in 251 strains of coagulase-negative Staphylococcus (CoNS) isolated from subclinical goat mastitis, as well as to determine the sensitivity and specificity of the nitrocefin and disk diffusion methods to detect penicillin resistance, in comparison with the polymerase chain reaction (PCR). The isolates were evaluated for the presence of the blaZ and mecA genes, β-lactamase production, and susceptibility to penicillin. Of the total isolates, 228 (91%) carried the blaZ gene and, among these, 144 (63%) were positive for β-lactamase production. Resistance to penicillin was observed in 125 of the isolates, of which 96.8% carried the blaZ gene. The sensitivity of the phenotypic methods to detect β-lactamase production was low, but their specificity was high; the Kappa coefficient showed a poor agreement between the phenotypic methods and PCR. The mecA gene was detected in only 3% of the isolates, which were identified as belonging to the species: S. capitis subsp. ureolyticus, S. caprae, S. warneri, S. sciuri, S. simulans, and S. cohnii subsp. urealyticum. Coagulase-negative Staphylococcus are important mastitis-causing pathogens in goat and harbor the blaZ and mecA genes related to resistance to β-lactam antimicrobials. The sensitivity of the nitrocefin and disk diffusion methods to detect penicillin resistance is low in relation to that of PCR.
Keywords: Staphylococcus; antimicrobial resistance; β-lactamase; blaZ; mecA